The nurses’ uniform in pediatrics, the opinion of children and nurses - Sanna, Piera; Sollami, Alfonso; Nicosia, Giuseppina; Dicembrino, Rita Bruna; Primosa, Flavia; La Sala, Rachele; Marletta, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: The nursing uniform represents a non-verbal mean of communication which in the case of children can arouse positive or negative emotions. The first study conducted on a sample of 107 children, aimed to define their preferences on different models of decorated nursing uniforms; the second one conducted on 101 nurses to understand the preferences, the meanings attributed to the uniform and their availability to adapt it according to the preferences expressed by the children. Methods: We conducted an observational study with a qualitative approach. For the first objective with the children, a visual stimulus was used, showing 6 models of uniform: the traditional plus 5 models of different colors and themes (cartoons characters and videogames). For the second objective with the nurses, in addition to reproducing the same visual stimulus, a semi-structured questionnaire was used. Results: Children and nurses seem to be in perfect accord, because in both groups, color models were the most chosen. Nurses defined their uniform with terms of particular moral, intellectual and professional value and declared themselves available to align with the preferences of the children. Conclusions: This study leaves little doubt about preferences; it also represents the true originality of the study because almost never in the literature have been compared the point of views of children and professionals, generally favoring the comparison between children and care givers. Our findings could represent a further landmark for guiding the choices of health organizations on currencies to be adopted in the pediatric field. (www.actabiomedica.it)